Papillary Fibroelastoma of the Right Ventricular Free Wall - Tetsuya Niino; Satoshi Unosawa (Case Reports in Surgery)
Papillary fibroelastoma is a rare benign cardiac tumor that usually arises from the valvular endocardium and its development in the cardiac chambers is extremely rare. A 52-year-old woman complained of palpitations and echocardiography revealed a cardiac tumor. Resection was performed via the right ventricle and main pulmonary artery under cardiopulmonary bypass. Histological examination of the resected tumor showed that it was a papillary fibroelastoma. The patient’s postoperative course was unremarkable and no complications have been detected on followup.